Rentabilidade e risco da produção de café sombreado no Maciço de Baturité, Ceará - Lima, Vitória Figueiredo (2023)
Coffee growing is one of the most important agricultural activities in the world, with a significant impact on the global economy. Coffee is one of the most traded commodities on the international market, playing a fundamental role in the lives of millions of people around the world. The economic and cultural importance is significant, but there are significant challenges related to production, trade and sustainability. With increasing awareness of environmental and social issues, the coffee industry is undergoing important changes to face these challenges and ensure a sustainable future for this commodity so appreciated around the world, this being the case with coffee production in the Massif de Baturité in the state of Ceará, Brazil. This research shows that although coffee production in the state of Ceará is relatively small, the quality is excellent, with a predominance of 70% originating in the Massif de Baturité region. Analyzing the risk of this crop is very important for the local community, therefore, the question arises: do shade coffee producers in the Baturité Massif carry out profitable exploitation, considering all the risks inherent to their production? The objective, then, is to analyze the profitability and risk of shaded coffee production in the Baturité Massif, state of Ceará, as well as to carry out the technical and economic characterization of coffee producers in the Baturité Massif and analyze profitability and risk of coffee producers to understand the agricultural production system practiced in the region, in addition to contributing to the development of public policies aimed at improving the development of this culture locally, strengthening associations and encouraging the use of more efficient cultivation techniques for production . As initial analysis methods, factorial and grouping analysis are used using the SPSS Statistics 20 software and, for risk analysis, the Monte Carlo method is used to characterize producers and identify economic profitability and the degree of risk of said production. It is concluded that production presents low risk, being quite profitable, with a 94% probability of the profit being greater than the average explored in the analysis.